1999
DOI: 10.1111/j.1574-6968.1999.tb13573.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and molecular characterization of the citrate utilizationcitMCDEFGRPcluster ofLeuconostoc paramesenteroides

Abstract: The citMCDEFGRP cluster from Leuconostoc paramesenteroides involved in citrate utilization was cloned and its nucleotide sequence determined. Homology of the inferred gene products with characterized enzymes reveals that citP encodes the citrate permease P, citC the citrate ligase and citDEF the subunits of the citrate lyase of Leuconostoc. Moreover, it suggests that citM encodes a Leuconostoc malic enzyme. Analysis of citrate consumption by and citrate lyase activity of Lc. paramesenteroides J1[pCITJ1] showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…CitE has been confirmed as an ATP-independent citrate lyase in various other bacteria [30][31][32]. Unexpectedly, in the present study, we found that ATP inhibited the citrate cleavage activity of CitE.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…CitE has been confirmed as an ATP-independent citrate lyase in various other bacteria [30][31][32]. Unexpectedly, in the present study, we found that ATP inhibited the citrate cleavage activity of CitE.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, we showed that MtbCitE was Mg 2+ dependent, and ATP could inhibit citrate cleavage activity. These findings indicated that the biochemical function of MtbCitE differed from that of other bacterial citrate lyases, including those from Escherichia coli [30], Klebsiella pneumoniae [31], and Leuconostoc paramesenteroides [32]. These previously described citrate lyase enzymes consist of an ATP-independent complex composed of six copies of each subunit, α, β, and γ.…”
Section: Discussionmentioning
confidence: 94%